Penyuluhan Pentingnya Pemberian Makanan Pendamping ASI (MP-ASI) Pada Anak Usia 6-8 Bulan Di Wilayah Kerja Puskesmas Botania - Erika Fariningsih; Yulinda Laska; Jihan Febiyanti (Lembaga Pengembangan Kinerja Dosen, 2024)
The complementary feeding of breast milk is additional food given to infants after the age of 6 months. Although breast milk is the best food for infants, after the age of >6 months, infants require more vitamins, minerals, proteins, and carbohydrates. The provision of complementary feeding aims to train and familiarize infants to consume foods that contain the nutrients needed by their bodies as they grow older. This community service activity uses a method of health education through providing information to the community about the importance of nutrition for children to prevent stunting, involving the roles of lecturers, health center officials, cadres, and students as responsible parties in community service. There were 17 mothers of toddlers who participated. With the implementation of community education at the integrated health service post (posyandu) regarding complementary feeding of breast milk for infants aged 6-8 months, the community gains a better understanding of the benefits of complementary feeding for infants aged 6-8 months.